DIVERSE ASPECTS OF LOCAL FISCAL CAPACITY – CASE STUDY OF POLAND - Elżbieta Malinowska-Misiąg (Polityki Europejskie, Finanse i Marketing)
The structure of the financial system of local government units (LGUs) determines the efficiency of its operation and development opportunities. Such a system should take into account both appropriately assigned sources of its own revenues as well as properly estimated expenditure needs, and equalization transfers. This paper focuses on the revenue side, more precisely – on the fiscal capacity of local governments. The paper begins by analyzing the concept of fiscal capacity in foreign and Polish literature. Then, three different types of fiscal capacity are distinguished, which is justified by the different purposes for which such capacities can be used. The remainder of the paper presents the amounts of fiscal capacity of various types of Polish LGUs in 2010-2017. An attempt was also made to identify external factors affecting the amount of this capacity.